2011
DOI: 10.1111/j.1600-6143.2011.03717.x
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Thrombosis Is a Potentially Preventable Complication in Clinical Islet Transplantation

Abstract: Percutaneous transhepatic portal access avoids surgery, but is rarely associated with bleeding or portal venous thrombosis. We herein report our large, single-center experience of percutaneous islet implantation, and evaluate risk factors of portal vein thrombosis and graft function. Prospective data was collected on 268 intraportal islet transplants (122 subjects). A portal venous Doppler ultrasound was obtained on Days 1 and 7 days posttransplant. Therapeutic heparinization, complete ablation of the portal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
80
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 29 publications
(39 reference statements)
2
80
0
1
Order By: Relevance
“…As previously reported, 34 and also in our series, a moderate increase of PVP was recorded after PIPIAT: this finding, often recorded after islet transplant, was already demonstrated to be strictly correlated to the number/volume of infused islets and the number of transplant procedures. 35 PVP increase is usually lower in autotransplantation than in allotransplantation, during which a higher islet mass is usually infused.…”
supporting
confidence: 70%
“…As previously reported, 34 and also in our series, a moderate increase of PVP was recorded after PIPIAT: this finding, often recorded after islet transplant, was already demonstrated to be strictly correlated to the number/volume of infused islets and the number of transplant procedures. 35 PVP increase is usually lower in autotransplantation than in allotransplantation, during which a higher islet mass is usually infused.…”
supporting
confidence: 70%
“…They also further investigated whether partial portal thrombosis was associated with detrimental loss of islet functional reserve. The incidence of portal thrombosis was low (3.2 %); despite partial portal thrombosis there was no detectable loss of islet graft function as measured by the SUITO index or insulin requirements [13,14]. Furthermore, Bucher et al [15] reported no association between portal thrombosis and increased IP pressure in islet autograft and allogeneic transplants when they limited the tissue volume infused to a mean of 13 cc [15].…”
mentioning
confidence: 98%
“…A previous report from an international multicenter trial suggested that covert, underlying thrombophilic tendencies (protein C, S, antithrombin III, factor v Leiden deficiencies, or presence of antiphospholipid antibodies) may potentially exacerbate the risk of portal thrombosis after islet transplantation [12]. In a large, single-center prospective series of 268 consecutive IP islet allo-transplants conducted over 11 years, the Edmonton group recently reported their incidence of portal venous thrombosis [13]. Kawahara et al analyzed the contributory factors leading to partial thrombosis, including standard liver volume (SLV), packed cell volume, and acute portal pressure rise after islet transplantation, assuming that a smaller liver volume would be likely to have less capacity for embolized IP tissue.…”
mentioning
confidence: 99%
“…Intraportal islet infusion can trigger hepatic false aneurysm [60], portal vein thrombosis [61], and acute hepatic steatosis [62]. Recently, the intrahepatic location of islet transplantation has been suggested to be a potential cause for islet graft failure and increase in hypoglycemic incidence.…”
Section: The Option Of Alternative Sites For Islet Transplantationmentioning
confidence: 99%